2016
DOI: 10.4049/jimmunol.1600033
|View full text |Cite
|
Sign up to set email alerts
|

Direct IL-6 Signals Maximize Protective Secondary CD4 T Cell Responses against Influenza

Abstract: Memory T cells can often respond against pathogens that have evaded neutralizing antibodies and are thus key to vaccine-induced protection, yet the signals needed to optimize their responses are unclear. Here, we identify a dramatic and selective requirement for IL-6 to achieve optimal memory CD4 T cell recall following heterosubtypic influenza A virus (IAV) challenge of mice primed previously with wild-type or attenuated IAV strains. Through analysis of endogenous T cell responses and adoptive transfer of IAV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…In viral infection models, IL‐6‐mediated enhancement of expansion and functional memory formation of T cells were also reported to exert immune‐stimulatory effects . However, a functional relevance of IL‐6 in the memory formation of tumor‐specific T‐cell responses remains to be elucidated, and thereby further intensive investigations on this subject will be required.…”
Section: Inflammation‐prone Environments Tend To Be Immune‐suppressivementioning
confidence: 99%
See 1 more Smart Citation
“…In viral infection models, IL‐6‐mediated enhancement of expansion and functional memory formation of T cells were also reported to exert immune‐stimulatory effects . However, a functional relevance of IL‐6 in the memory formation of tumor‐specific T‐cell responses remains to be elucidated, and thereby further intensive investigations on this subject will be required.…”
Section: Inflammation‐prone Environments Tend To Be Immune‐suppressivementioning
confidence: 99%
“…53 In viral infection models, IL-6-mediated enhancement of expansion and functional memory formation of T cells were also reported to exert immune-stimulatory effects. 54,55 However, a functional relevance of IL-6 in the memory formation of tumor-specific T-cell responses remains to be elucidated, and thereby further intensive investigations on this subject will be required. It is noteworthy that viral infection-induced early IL-6 production is a part of acute inflammation with robust up-regulation of various other cytokines F I G U R E 3 Transcription factor c-Maf dampens the anti-tumor activity of CD4 + T cells.…”
Section: Inflammation-pron E Environme Nts Tend To Be Immune-supprementioning
confidence: 99%
“…Elevated IL-6 is viewed as a distinctly proinflammatory cytokine, promptly activating the host defense system to perform diverse functions[ 17 ]. Early and direct IL-6 signals were involved in aiding immune responses at the site of infection during heterosubtypic challenge[ 18 ]. Some studies reported that IL-6 was a more suitable parameter in cases of severe systemic inflammation for patients with severe liver impairment than WBC or CRP[ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The antigen-specific regulation of inflammatory responses provides an additional means by which the immune response can generate alarm signals during infections with pathogens that possess means to evade detection by the innate immune-sensing mechanisms discussed earlier [ 136 ]. It also provides a means whereby experienced memory cells can modulate the effector functions of the ensuing adaptive response of expanded secondary effector T cells that arise from resting memory T cell precursors during recall [ 137 ].…”
Section: Inflammation and The Generation Of Adaptive Immune Responmentioning
confidence: 99%
“…Following secondary IAV infection, the earlier and more robust inflammatory response induced by memory CD4 T cells correlates with improved control of the virus in the lung [ 133 ]. Our recent findings show that one innate inflammatory cytokine involved in this response, IL-6, plays a central role in maximizing the multicytokine-producing potential of secondary CD4 + T effector cells that accumulate in the lung at the peak of the recall response [ 137 ] ( Figure 2 ). In murine and human systems, multicytokine-producing potential, or the ability to coproduce TNF, IL-2, and IFN- γ , is associated with the ability of memory T cell responses to protect against numerous viral, bacterial, and parasitic pathogens [ 120 ].…”
Section: Inflammation and The Generation Of Adaptive Immune Responmentioning
confidence: 99%